Development of Arabic comics as a learning media for reading skills at Sumenep State Islamic High School - Mufidha, Ulfatul; Sari, Risna Rianti (Abjadia : International Journal of Education, 2025)
The purpose of this study was to determine the process of developing comics as a medium for learning maharah qiro'ah, and to test the effectiveness of comics as a medium for learning maharah qiro'ah in class XI of Madrasah Aliyah Negeri Sumenep. This study is a research and development (Research and Development) using the 4D model, which includes four stages: define, design, development, and disseminate. The data sources in this study were students of class XI and one Arabic language subject teacher. The results of this study are learning media in the form of Arabic comics that have been validated showing that: validation from material experts got a score of 100% in the "very valid" category, validation from design experts got a score of 95.2% in the "very valid" category, validation from language experts with a score of 100% in the "very valid" category. The results of the field trial showed that the trial in small groups got a score of 86% in the "effective" category, while the trial in large groups got a score of 81% in the "effective" category. The Arabic subject teacher response questionnaire obtained a score of 87.60% in the "very practical" category, the student response questionnaire in the small group trial obtained a score of 89.5% in the "very practical" category, and the student response questionnaire in the large group trial obtained a score of 81.9% in the "very practical" category.